Telomeres and cardiovascular disease - Buxton, Jess (Henry Stewart Talks, 2018)
Vertebrate telomere structure and telomerase, Telomeres and monogenic disease, Telomeres and ageing, Factors that affect leukocyte telomere length (LTL), Telomere length and stressful life events, Telomeres and cardiovascular disease risk, Common genetic variants associated with LTL, A causal role for LTL in CVD: evidence and potential mechanisms